"I hate being a burden": The patient perspective on carer burden in amyotrophic lateral sclerosis. Issue 5 (17th August 2016) - Foley, Geraldine; Timonen, Virpi; Hardiman, Orla
Abstract: Research has shown that family caregivers of ALS patients encounter carer burden. Studies that have investigated the impact of caring on family in ALS have reported predominantly from the family caregiver perspective. We undertook in-depth qualitative interviews with a diverse group of ALS patients ( n = 34) sampled from the Irish ALS population-based register and explored their experiences of receiving care from family members and from formal service providers. Interviews were audio recorded and transcribed and data were coded to identify psychosocial processes. Findings showed that patients perceived their care as a burden on family and had concerns about the adverse effects that caring had on family caregivers. However, participants also resisted being a burden on family and they provided emotional support to their family. Participants felt a strong sense of obligation towards family and their concern about family members shaped their expressed preferences for care. We identified that the caring process between ALS patients and their family is often bi-directional, leading in some cases to the patient experiencing carer burden. In conclusion, greater attention in ALS research and practice to patients' supportive roles in family is required to counterbalance the already strong focus on family caregiver burden.